Per- and polyfluoroalkyl substances (PFAS), trace elements and life history parameters of mass-stranded common dolphins (Delphinus delphis) in New Zealand. (December 2021) - Stockin, K.A.; Yi, S.; Northcott, G.L.; Betty, E.L.; Machovsky-Capuska, G.E.; Jones, B.; Perrott, M.R.; Law, R.J.; Rumsby, A.; Thelen, M.A.; Graham, L.; Palmer, E.I.; et al.
Abstract: Profiles of 33 PFAS analytes and 12 essential and non-essential trace elements were measured in livers of stranded common dolphins ( Delphinus delphis ) from New Zealand. PFAS concentrations reported were largely comparable to those measured in other marine mammal species globally and composed mostly of long-chain compounds including perfluorooctanesulfonic acid (PFOS), perfluorododecanoic acid (PFDoDA), perfluorotridecanoic acid (PFTrDA) and perfluorooctanesulfonamide (FOSA). PFAS profiles did not vary significantly by location, body condition, or life history. Notably, significant positive correlations were observed within respective PFAS and trace elements. However, only negative correlations were evident between these two contaminant types, suggesting different exposure and metabolic pathways. Age-associated concentrations were found for PFTrDA and four trace elements, i.e. silver, mercury, cadmium, selenium, indicating differences in the bioaccumulation biomagnification mechanisms. Overall, our results contribute to global understanding of accumulation of PFAS by offering first insights of PFAS exposure in cetaceans living within South Pacific Australasian waters. Highlights: First PFAS assessment of cetaceans in Australasian waters PFAS concentrations reported in New Zealand common dolphins largely comparable to those measured in similar small delphinids globally. Most PFAS compose long-chain compounds including PFOS, PFDoDA, PFTrDA and FOSA. Negative correlations between contaminant types suggest different exposure pathways and sources. Age-associated concentrations were found for PFTrDA and silver, mercury, cadmium, selenium, indicating differences in the bioaccumulation/biomagnification mechanisms.